Placental growth factor testing for suspected pre‐eclampsia: a cost‐effectiveness analysis. (17th July 2019) - Duhig, KE; Seed, PT; Myers, JE; Bahl, R; Bambridge, G; Barnfield, S; Ficquet, J; Girling, JC; Khalil, A; Shennan, AH; Chappell, LC; Hunter, RM
Abstract : Objective: To calculate the cost‐effectiveness of implementing PlGF testing alongside a clinical management algorithm in maternity services in the UK, compared with current standard care. Design: Cost‐effectiveness analysis. Setting: Eleven maternity units participating in the PARROT stepped‐wedge cluster‐randomised controlled trial. Population: Women presenting with suspected pre‐eclampsia between 20 +0 and 36 +6  weeks' gestation. Methods: Monte Carlo simulation utilising resource use data and maternal adverse outcomes. Main outcome measures: Cost per maternal adverse outcome prevented. Results: Clinical care with PlGF testing costs less than current standard practice and resulted in fewer maternal adverse outcomes. There is a total cost‐saving of UK£149 per patient tested, when including the cost of the test. This represents a potential cost‐saving of UK£2, 891, 196 each year across the NHS in England. Conclusions: Clinical care with PlGF testing is associated with the potential for cost‐savings per participant tested when compared with current practice via a reduction in outpatient attendances, and improves maternal outcomes. This economic analysis supports a role for implementation of PlGF testing in antenatal services for the assessment of women with suspected pre‐eclampsia. Tweetable abstract: Placental growth factor testing for suspected pre‐eclampsia is cost‐saving and improves maternal outcomes. Tweetable abstract: Placental growth factor testing for suspected pre‐eclampsia is cost‐saving and improves maternal outcomes.